THE EFFECT OF GREEN ACCOUNTING PRACTICE ON MAQASHID SHARIA PERFORMANCE IN ISLAMIC BANKS - Khasanah, Amirah Arifah; Laela, Sugiyarti Fatma (JURNAL AKUNTANSI DAN AUDITING, 2024)
The purpose of this study is to analyze the effect of green accounting practice on maqashid sharia performance in Islamic banks. This research data used secondary data of 16 Islamic banks in Indonesia. Smart PLS 4 with the SEM-PLS model is the software used to test the effect between the dependent variable, namely the maqashid sharia index which is proxied in educating individuals; establishing justice; and promoting welfare on the independent variable, namely green accounting practice which is also proxied by green investment, green initiatives, and green activity management. Meanwhile, the control variables used in this study aim to control causality in obtaining a more complete empirical model measured using bank size. The results indicate that green investment, green initiative, and green activity management that fulfil the category in representing the practice of green accounting in islamic banks. The implementation of maqashid sharia in Islamic banks is only represented by educating individuals and promoting welfare. Furthermore, the results of the effect test in this study are green accounting practice have a negative significant effect on maqashid sharia performance in islamic banks. While bank size proxied as control variable have a positive significant effect on maqashid sharia performance.